2022
DOI: 10.1093/ofid/ofac424
|View full text |Cite
|
Sign up to set email alerts
|

Surge in Incidence and Coronavirus Disease 2019 Hospital Risk of Death, United States, September 2020 to March 2021

Abstract: Objectives Studies of the early months of the COVID-19 pandemic indicate that patient outcomes may be adversely affected by surges. But the impact on in-hospital mortality during the largest surge to date, September 2020-March 2021, has not been studied. This study aimed to determine if in-hospital mortality was impacted by the community surge of COVID-19. Methods A retrospective cohort study of 416,962 adult COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thus, our finding may be a result of our retrospective design or due to unaccounted variability in disease severity and duration, corticosteroid timing, dose, indication, and days of therapy, because anecdotally we observed corticosteroid prescriptions substantially incongruent with recommended regimens [ 95 ] in our population (D. G., unpublished observations, 2022). Other explanations include surges in inpatients with COVID-19, as has been previously reported during the time period of our study [ 96 , 97 ], particularly in Hispanic/Latino patients [ 96 ] and for community hospitals [ 97 ]. Our observation of increased COVID-19 mortality associated with temporal surges in COVID-19 inpatients at our hospital supports this possibility.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, our finding may be a result of our retrospective design or due to unaccounted variability in disease severity and duration, corticosteroid timing, dose, indication, and days of therapy, because anecdotally we observed corticosteroid prescriptions substantially incongruent with recommended regimens [ 95 ] in our population (D. G., unpublished observations, 2022). Other explanations include surges in inpatients with COVID-19, as has been previously reported during the time period of our study [ 96 , 97 ], particularly in Hispanic/Latino patients [ 96 ] and for community hospitals [ 97 ]. Our observation of increased COVID-19 mortality associated with temporal surges in COVID-19 inpatients at our hospital supports this possibility.…”
Section: Discussionmentioning
confidence: 80%
“…However, previous research has evaluated these disorders in relation to severe COVID‐19 and COVID‐19 VE [ 26 , 27 , 28 , 29 , 30 , 31 ]. Tenth, data on neurodevelopmental disorders (aside from attention‐deficit hyperactivity disorder) were also not examined but have been reported in another VISION Network study [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of the Veteran’s Healthcare databases revealed a doubling of ICU mortality during high-demand versus low-demand periods (5). Significant mortality increases occurred (OR 1.23 vs. baseline) in the United Kingdom as the occupancy of intensive care beds exceeded 85% (6) and in the United States during peak pandemic weeks (OR 1.37 vs. baseline) (7). Investigators have found effects on mortality during surge for specific conditions as well—for example, an increase in non-ST-elevation myocardial infarction mortality of over 50% (8).…”
mentioning
confidence: 99%